The Influence of Problem-Oriented Project-Based Learning (POPBL) on Students' Creative Thinking Skills - Francisco, Rendi; Ibrohim, Ibrohim; Susilo, Herawati (BIOEDUKASI, 2024)
Problem and project-based learning can develop students' creative thinking skills because students will learn better if they engage in meaningful learning activities. The implementation of this study uses the Problem-Oriented Project-Based Learning (POPBL) model to direct students to create creative products. This study aims to measure the effect of problem-based learning and projects on the creative thinking skills of grade X students of SMA Negeri 10 Malang. The method used in this study is quasi-experimental research using Pretest Post-test Nonequivalent Control Group Design. The results of the essay test were analyzed using the analysis of covariance (ANCOVA) test. The results showed that the application of Problem-Oriented Project-Based Learning (POPBL) had a significant effect on students' creative thinking skills. These findings suggest that problem- and project-based learning models can develop students' capacity for creative thinking skills.